A micro-analytical approach to cognitive engagement during Team Based Learning (TBL) in an undergraduate medical curriculum - Wong, Joey Ying Hao (2017)
Purpose: This study aimed to determine and analyze the levels of cognitive engagement during Team Based Learning (TBL) phases in an undergraduate medical curriculum. Methods: The TBL phases were Preparation (Prep), Individual Readiness Assurance (IRA), Team Readiness Assurance (TRA), Burning Questions (BQs), Application Exercise (AE) split into discussion and reporting. This was achieved by using a validated self-reporting instrument to measure engagement levels in real time. The study surveyed a class of medical undergraduates in one TBL session (males=70, females=36, total=106). A total of 6 surveys were answered with 1 survey for each phase. Data were analyzed using one-way repeated measures ANOVA. Results: Cognitive engagement levels for students were constantly higher during the session compared to when they were preparing beforehand using recorded lectures. For example, there was an increase in engagement levels from Prep (3.65, SD=1.17) to IRA (4.15, SD=1.70), p<0.001. Additionally, fluctuations were seen in engagement levels during TBL sessions. There were peaks at TRA (4.35, SD=1.81) and AE discussion (4.19, SD=1.53) and troughs at BQ and AE reporting. These fluctuations corresponded to the amount of team discussion, with more team interaction having more engagement. Conclusion: TBL is an engaging format for learning to which students can actively think and learn.